Perancangan Aplikasi Desain Motor Klasik Custom Menggunakan Teknologi Augmented Reality - Palendeng, Chrisye Imanuel Luther; Tulenan, Virginia; Sengkey, Rizal (Jurnal Teknik Informatika, 2020)
Custom classic motorbike is a motorbike modification that is done to suit the wishes of the owner of the motorbike, which is to become a classic motorbike or an old motorcycle. Classic motorcycle has several types, namely chopper, cafe racer, tracker, scrambler, japstyle, and many more. Several years ago there was an assumption among people that riding motorbikes classic category, were no longer a means of transportation, had become a hobby or lifestyle. This application was created using the Multimedia Development Life Cycle (MDLC) method. This application was built using Unity software and this application will run on the Android platform. Based on the results of testing and questionnaires, then as much as 87.5% of respondents approved the application of this classic custom motorcycle application is very interesting and 81% of respondents said it was facilitated by this custom classic motorbike design application.